177Lu‐5‐Fluorouracil a potential theranostic radiopharmaceutical: radiosynthesis, quality control, biodistribution, and scintigraphy. (22nd July 2016) - Rasheed, Rashid; Tariq, Saleha; Naqvi, Syed Ali Raza; Gillani, Syed Jawad Hussain; Rizvi, Faheem Askari; Sajid, Muhammad; Rasheed, Shahid
Abstract : The aim of this study is to develop 177 Lu‐5‐Flourouracil as a potential cancer therapeutic radiopharmaceutical. 5‐Flourouracil (5‐FU) is widely accepted as an anticancer drug of broad spectrum fame. The labeling of 5‐FU was carried out at different set of experimental conditions using high specific activity of 177 LuCl3 . The optimum conditions for maximum radiochemical yield was set: 5‐FU (5 mg), 177 LuCl3 (185 MBq), diethylenetriaminepentaacetic acid (10 µg), reaction volume (2 mL), pH (5.5), temperature (80°C), and reaction time (20 min). The radiochemical labeling was assessed with Whatman No. 2 paper, instant thin layer chromatographic, and radio‐HPLC, which revealed >94% labeling results with sufficient stability up to 6 h. Serum stability study also showed 177 Lu‐5‐FU promising stability. Biodistribution study in normal rats and rabbits showed liver, stomach, kidney, and heart as area of increased tracer accumulation just after injection, which decreased to 1.4%, 0.4%, 0.2%, and 0.39% ID/g, respectively, after 72 h. Glomerular filtration rate and cytotoxicity study results of 177 Lu‐5‐FU showed it had no adverse effect on renal function and nontoxic to blood cells. The promising characteristics of 177 Lu‐5‐FU, that is, clever elimination from kidney and nontoxic nature toward blood cells make it the radiopharmaceutical for further testing in patients for therapeutic purposes. Abstract : 5‐Flourouracil (5‐FU) is widely accepted as an anti‐cancer chemotherapeutic drug of broad spectrum fame. The labeling of 5‐FU was carried out using β‐rays emitter radionuclide (lutetium‐177) to develop therapeutic radiopharmaceuticals.